Voriconazole for secondary prophylaxis of invasive fungal infections in allogeneic stem cell transplant recipients: results of the VOSIFI study - Cordonnier, Catherine; Rovira, Montserrat; Maertens, Johan; Olavarria, Eduardo; Faucher, Catherine; Bilger, Karin; Pigneux, Arnaud; Cornely, Oliver A.; Ullmann, Andrew J.; Bofarull, Rodrigo Martino; de la Cámara, Rafael; Weisser, Maja; et al. (Haematologica, the hematology journal, 2010)
BACKGROUND: Recurrence of prior invasive fungal infection (relapse rate of 30-50%) limits the success of stem cell transplantation. Secondary prophylaxis could reduce disease burden and improve survival. - DESIGN AND METHODS: A prospective, open-label, multicenter trial was conducted evaluating voriconazole (4 mg/kg/12 h intravenously or 200 mg/12 h orally) as secondary antifungal prophylaxis in allogeneic stem cell transplant recipients with previous proven or probable invasive fungal infection. Voriconazole was started 48 h or more after completion of conditioning chemotherapy and was planned to be continued for 100-150 days. Patients were followed for 12 months. The primary end-point of the study was the incidence of proven or probable invasive fungal infection. - RESULTS: Forty-five patients were enrolled, 41 of whom had acute leukemia. Previous invasive fungal infections were proven or probable aspergillosis (n=31), proven candidiasis (n=5) and other proven or probable infections (n=6); prior infection could not be confirmed in three patients. The median duration of voriconazole prophylaxis was 94 days. Eleven patients (24%) died within 12 months of transplantation, but only one due to systemic fungal disease. Three invasive fungal infections occurred post-transplant: two relapses (one candidemia and one fatal scedosporiosis) and one new zygomycosis in a patient with previous aspergillosis. The 1-year cumulative incidence of invasive fungal disease was 6.7±3.6%. Two patients were withdrawn from the study due to treatment-related adverse events (i.e. liver toxicity). - CONCLUSIONS: Voriconazole appears to be safe and effective for secondary prophylaxis of systemic fungal infection after allogeneic stem cell transplantation. The observed incidence of 6.7% (with one attributable death) is considerably lower than the relapse rate reported in historical controls, thus suggesting that voriconazole is a promising prophylactic agent in this population.